If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 91 = 7(X + 7) Reorder the terms: 91 = 7(7 + X) 91 = (7 * 7 + X * 7) 91 = (49 + 7X) Solving 91 = 49 + 7X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7X' to each side of the equation. 91 + -7X = 49 + 7X + -7X Combine like terms: 7X + -7X = 0 91 + -7X = 49 + 0 91 + -7X = 49 Add '-91' to each side of the equation. 91 + -91 + -7X = 49 + -91 Combine like terms: 91 + -91 = 0 0 + -7X = 49 + -91 -7X = 49 + -91 Combine like terms: 49 + -91 = -42 -7X = -42 Divide each side by '-7'. X = 6 Simplifying X = 6
| 6x-7=3x+4+2x+1 | | 6m+3+5-9m= | | 3(9)+y=-8 | | C-7.4=-4 | | -3(3x-1)+2(5x-4)=16 | | 3(8)+y=-8 | | ×=-5/7y=14/17 | | 64+32+h=180 | | 9/3.5 | | 3(7)+y=-8 | | n+11=2n+18 | | 3(6)+y=-8 | | 5(-2x-6)=8x | | 1/3x-3y | | 3(4)+y=-8 | | 9y-3(y+4)=12 | | (2p+15)+(p+15)+p=180 | | 6/8=x/x-4 | | 2x+5-x-5=0 | | 3(2x+1)=30x+20 | | 3(3)+y=-8 | | 7x+7y=135+2x+2y | | 2x^4-15x^2+28=0 | | 2p+15+p+15+p=180 | | 48=4x-2(-26+8x) | | 2+q=4.5 | | 82+49+z=180 | | 53-2x=3x-175 | | 5x+8+4x=2x-13 | | 4/5x-3=21 | | h(t)=-16t^2+8t+10 | | 27-2n=17 |